Field investigation of Bithynia funiculata, intermediate host of Opisthorchis viverrini in northern Thailand - Radchadawan Ngern-Klun (2018)
A survey of freshwater snail, Bithynia funiculata, was conducted in four locations, Doi Saket, Mueang, Saraphi and Mae Rim Districts of Chiang Mai Province, northern Thailand, between June and October, during the rainy season of 2004. A total of 2,240 snails was collected and classified into 7 families and 15 genera; of which 352 B. funiculata were obtained. B. funiculata was found most abundant in July and September. The infection rate of trematode cercariae in B. funiculata was 9.6% (19/352), while that of pleurolophocercous was 0.3% (1/352). Virgulate cercaria was the most common type, followed by lophocercous, monostome and pleurolophocercous. B. funiculata prefers habitats with clear water, which was less than 30 cm depth, temperatures between 24.48 and 31.78°C, dissolved oxygen 2.03-7.66 mg/l, saturated dissolved oxygen 26.70-95.00%, conductivity 0.000-0.2642 mS/cm, turbidity 16.00-288.00 NTU and pH 6.58-7.56. Geographic Information System (GIS) analysis using loose soil mixed with clay revealed that the breeding grounds of this snail species was in the paddy fields and village environs of the Ping, Kuang and Fang river basins.